Digital Constitutionalism and Human Rights: A Comparative Constitutional Response to Global Technological Challenges: Digital Constitutionalism and Human Rights: A Comparative Constitutional Response to Global Technological Challenges - Ardhy Gumilar; Abdul Latif; Supaphorn Akkapin (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2026)
The rapid growth of digital technologies has reshaped communication, governance, and the interpretation of constitutional rights. This study examines how constitutionalism, traditionally designed to limit state power, must adapt to new digital challenges such as surveillance, data exploitation, algorithmic governance, and restrictions on online expression. Using a normative-comparative approach, this study examines constitutional texts, landmark decisions, and regulatory frameworks from Germany, India, South Africa, and Indonesia, alongside international instruments such as the ICCPR and the GDPR. Findings highlight three main patterns. First, privacy and data protection are increasingly recognized as constitutional rights, although this recognition is inconsistent across jurisdictions. Second, digital freedom of expression remains a contested issue, with some courts applying proportionality while others rely on administrative controls. Third, responses to state surveillance reveal a global trend toward stronger safeguards; yet, significant gaps persist in developing contexts, such as Indonesia. This article advances the concept of digital constitutionalism as a paradigm shift extending constitutional protections beyond the state to powerful technology corporations. Theoretically, it reframes constitutionalism in the digital era; practically, it offers normative guidance for courts and policymakers to reinforce digital rights. Ultimately, digital constitutionalism is vital not only for protecting individual rights but also for sustaining democracy in the digital age.